Understanding Crohn disease and ulcerative colitis - Zonderman, Jon (Understanding health and sickness series., 2000)
Written from a patient's perspective, this book provides timely information about how to obtain and maintain the highest quality of life possible while living with inflammatory bowel disease (IBD). Crohn disease and ulcerative colitis--together known as inflammatory bowel disease--are chronic illnesses of unknown origin. The inflammation within the intestinal tract (within the colon in ulcerative colitis, and anywhere from the mouth to the anus in Crohn disease) leads to some or all of the following clinical symptoms--diarrhea (with or without blood), abdominal pain, fever, and fatigue. The di.